2010
DOI: 10.1053/j.gastro.2010.03.038
|View full text |Cite
|
Sign up to set email alerts
|

Human Risk Allele HLA-DRB1*0405 Predisposes Class II Transgenic Ab0 NOD Mice to Autoimmune Pancreatitis

Abstract: Background & Aims Autoimmune pancreatitis (AIP) underlies 5%–11% of cases of chronic pancreatitis. An association between AIP and the HLA-DRB1* 0405/DQB1*0401 haplotype has been reported, but linkage disequilibrium has precluded the identification of predisposing HLA gene(s). We studied the role of single HLA genes in the development of AIP in transgenic mice. Methods CD4+ T cell-negative I-Aβ chain−/− (Ab0) mice develop AIP spontaneously, likely due to dysregulation of CD8+ T cell responses. We generated Ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 26 publications
(39 reference statements)
1
21
0
Order By: Relevance
“…Although the pathogenesis of AIP remains to be elucidated, several reports suggested that susceptibility to AIP may be related to certain MHC class II allele 28,29. In the present study, we found that gliadin exposure in gluten-sensitive transgenic mice showed chronic pancreatitis similar to human AIP.…”
Section: Discussionsupporting
confidence: 65%
“…Although the pathogenesis of AIP remains to be elucidated, several reports suggested that susceptibility to AIP may be related to certain MHC class II allele 28,29. In the present study, we found that gliadin exposure in gluten-sensitive transgenic mice showed chronic pancreatitis similar to human AIP.…”
Section: Discussionsupporting
confidence: 65%
“…Another disease observed in NOD mice is inflammation of the pancreas 25 that is also observed in the MRL/Mp and MRL/Mp-Fas models of AIP 26, 27 . Accordingly, Figures 4a, b and S2b, show inflammatory foci and high level of collagen in the endocrine (islet in Figure 4a, top left image) and exocrine pancreas that is infiltrated by T and B cells and neutrophils.…”
Section: Resultsmentioning
confidence: 81%
“…However, such models can be highly variable. Even though spontaneous AIP development has been reported previously in genetic backgrounds prone to develop autoimmunity [39], a genetic model of AIP with robust penetrance and phenotypic reproducibility on C57BL/6 background did not exist. Currently, the treatment options for AIP are limited.…”
Section: Discussionmentioning
confidence: 96%